Knowing Is Not Half the Battle: Impacts of the National Health Screening Program in Korea - Hyuncheol Bryant Kim; Suejin Lee; Wilfredo Lim (Institute of Labor Economics (IZA), 2017)
Health screening provides information on disease risk and diagnosis, but whether this promotes health is unclear. We estimate the impacts of the National Health Screening Program in Korea for diabetes, obesity, and hyperlipidemia. In this setting, information on disease risk and prompting for a secondary examination vary at different biomarker thresholds. We find evidence for increased diabetes medication and weight loss around the high risk threshold for diabetes, where information is combined with prompting for a secondary examination and subsequent medical treatment. However, we find no differences around other thresholds, where information is not combined with further intervention.
Keywords: I12; I18; 330; health behavior; hyperlipidemia; diabetes; obesity; information; health screening